Ricardo Palma University in the SCIMAGO INSTITUTIONS RANKINGS 2023: La universidad Ricardo Palma en el SCIMAGO INSTITUTIONS RANKINGS 2023 - De La Cruz-Vargas, Jhony A. (2023)
Scientific research has always played a fundamental role in promoting health and the progress of society as a whole. A recent editorial published in The Lancet has discussed plausible research scenarios and outlined a vision of the future in which research could be an instrument for an "equitable and sustainable world with better health for all".